Effectiveness of Ear Acupressure on Gestational Hypertension - Setiawandari, Setiawandari; Iswati, Retno Setyo; Rihardini, Tetty (EMBRIO: Jurnal Kebidanan, 2025)
Hypertensive disorders (HD) affect up to 10 percent of pregnancies worldwide. Gestational Hypertension 17 percent will progress to preeclampsia if left untreated. Acupressure has been used for centuries to treat a variety of symptoms associated with pregnancy and is also known to lower blood pressure in hypertension. However, the use of ear acupressure as an adjunct to conventional care for hypertensive disorders in pregnancy is underrepresented in the scientific literature. This study aimed to determine the effectiveness of ear acupressure on gestational hypertension. The research method employed a pre-experimental design with a one-group pre-post design. A sample of 15 people received antenatal care and ear acupressure. Analysis using the Paired T Test. The study's results showed a difference in the average blood pressure of primigravida women in the 2nd and third trimesters, both before and after ear acupressure, of 6 mmHg systolic and 4 mmHg diastolic. The results of the Paired t-test p equal 0.00. The conclusion is that ear acupressure affects the blood pressure of primigravida during the second and third trimesters.